Cross-country inequalities in the epidemiology of chronic kidney disease due to type 2 diabetes mellitus, 1990–2021: findings from the global burden of disease study 2021 - Shiyi Shan; Jiayao Ying; Jiali Zhou; Zeyu Luo; Jing Wu; Guangdian Shen; Denan Jiang; Lingzi Yao; Liying Zhou; Peige Song (Diabetology & Metabolic Syndrome, 2025)
Abstract Background Chronic kidney disease due to type 2 diabetes mellitus (CKD-T2DM) is a predominant and life-threatening complication of T2DM, with significant inequalities in its epidemiological features globally. This study aimed to examine cross-country inequalities in the epidemiology of CKD-T2DM from 1990 to 2021. Methods Data were extracted from the Global Burden of Disease (GBD) 2021 study. The epidemiological features of CKD-T2DM included age-standardized prevalence rate (ASPR), incidence rate (ASIR), and death rate (ASDR) from 1990 to 2021. The slope index of inequality (SII) and concentration index were applied to evaluate absolute and relative cross-country inequalities at global and regional scales in 1990 and 2021. Six inequality changing patterns were identified: worsening inequality in lower socio-demographic index (SDI) countries, improving inequality in lower SDI countries, worsening inequality in higher SDI countries, improving inequality in higher SDI countries, shift to higher burden in higher SDI countries, and shift to higher burden in lower SDI countries. Results Globally, from 1990 to 2021, the inequality in ASPR exhibited a worsening inequality in lower SDI countries pattern, with SII increasing from -161.96 (95% confidence interval [CI]: -292.64, -31.28) to -181.13 (95% CI: -302.25, -60.00) and concentration index from -0.03 (95%CI: -0.05, -0.02) to -0.04 (95%CI: -0.05, -0.02). The SII for ASIR showed a worsening inequality in higher SDI countries pattern, ranging from 9.44 (95% CI: 6.79, 12.08) to 11.65 (95% CI: 8.20, 15.10), while the concentration index exhibited an improving inequality in higher SDI countries pattern, ranging from 0.09 (95% CI: 0.06, 0.12) to 0.09 (95% CI: 0.06, 0.12). The SII for ASDR showed a worsening inequality in lower SDI countries pattern, ranging from -4.46 (95% CI: -6.44, -2.47) to -5.42 (95% CI: -7.92, -2.90), while the concentration index exhibited an improving inequality in lower SDI countries pattern, shifting from -0.13 (95% CI: -0.20, -0.07) in 1990 to -0.11 (95% CI: -0.18, -0.03) in 2021. Inequality patterns also varied across different geographic or socio-economic regions. Conclusions Our study revealed considerable cross-country inequalities in the epidemiology of CKD-T2DM, underscoring the necessity for tailored health interventions, international cooperation, and adequate healthcare investment across different regions to address these inequalities.